2007
DOI: 10.1021/ja075489b
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Chemical and Molecular Dynamics Study of the Coordination of Cm(III) in Water

Abstract: The study of the behavior of actinide ions in aqueous solution plays a fundamental role in the quest for a better understanding of actinide waste storage problems and separation processes. Considerable progress has been made both experimentally and computationally in recent years, with special attention given to the uranyl ion, 1,2 as well as trivalent lanthanide and actinide ions. Systematic studies of the aqueous trivalent lanthanide ion first coordination sphere show the number of water molecules changes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 11 publications
12
70
0
Order By: Relevance
“…In addition, many recent studies highlighted the failure of traditional fixed charge force fields to capture the main physical effects that govern interaction for highly charged ions in polar solvents [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many recent studies highlighted the failure of traditional fixed charge force fields to capture the main physical effects that govern interaction for highly charged ions in polar solvents [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…54 The standard deviations for both magnitudes have been collected in Table II. The comparison of quantum and classical geometries for the smaller hydrated ions (n = 1, 2, 4) is not as good as for the aqua ions with larger hydration numbers. This may be understood on the fact that the small hydrates have not 12 , where the second hydration shell appears to be too much distant from the hexahydrate. If these data are excluded, the standard deviation goes down to 0.09 Å.…”
Section: A Minimizationsmentioning
confidence: 99%
“…For Cm(III), Yang and Bursten 8 developed an intermolecular potential based on our hydrated ion model, [9][10][11] assuming a rigid ennea-coordination (nine-fold coordination) of the cation. Gagliardi et al 12 developed a Cm(III)-H 2 O intermolecular potential from high-level ab initio computation of this system where many-body interactions are included by means of the polarizable character of the water molecules and the ion, that are described by a perturbation theory-derived intermolecular potential (the NEMO approach). 13 Atta-Fynn et al 14 have developed another interaction potential including three-body corrections by fitting a ROHF potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
“…In such a way she can study also systems for which not enough experimental data are available, unlike when one uses semi-empirical force field. [54] L. Gagliardi has proven that multiconfigurational quantum chemistry is a powerful and useful tool in chemistry that can tackle difficult problems and not just a nice formalism, relegated to model systems. She has shown that the CASSCF/CASPT2 approach is a competitive alternative to DFT and thus a modern tool in quantum chemistry.…”
Section: Computational Chemistry At the Dpcmentioning
confidence: 99%